Fort Misery : These Men Chose Hell - Book 2 - Johnstone, William W.; Johnstone, J. A. (Thorndike, Maine : Center Point Large Print, 2025)
"Theyre not what youd call "the good guys." Theyre a mangy pack of despicable deserters, thieves, mutineers, and worse. But as condemned soldiers in an overstretched army, they were given a choice: death by hanging or serving out their time in a hell on earth. These men chose hell. Located at the farthest edge of the Yuma Desert, Fort Grierson is a magnet for trouble. Vicious attacks by marauding Apaches and gunslinging outlaws are practically a daily occurrence and the men holding down the fort are hardly any better. Hence the nickname Fort Misery."--
Keywords: United States. -- Army -- Military life; Fiction; Soldiers -- Fiction; Excavations (Archaeology) -- Fiction; Outlaws -- Fiction; Apache Indians -- Wars; Fiction; Fortification -- Arizona; Fiction; Frontier and pioneer life -- Fiction; Arizona -- Fiction; United States -- History -- 1865-1898; Fiction; Western fiction; Large print books